Studi Literatur Cara Menjadi Penyedia E-Katalog Pada LKPP Sebagai Lembaga Pengadaan Barang Dan Jasa Bagi Pelaku Usaha - Sinta Puspita Sari; Amyra Syalsabila; Silvi Yulianti; Sigit Djalu Purwoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Republic of Indonesia Government Goods and Services Procurement Policy Agency or LKPP RI for short. LKPP has made a big leap in the development of the e-catalog system by starting to involve SOEs. This research focuses on discussing the requirements and steps for business actors to become e-catalog providers. This research uses the literature study method. The results of this study found that the requirements for business qualifications for electronic catalog providers have six qualifications whose final decision is made by the head of LKPP. There are several criteria that must be met by business actors if they want to register their business in the LKPP e-catalog. There are two types of goods and services received, namely, first general goods and services including goods and services needed by K / L, standard or standardizable goods / services, and recurring goods / services needs. The second type of innovation products, namely products determined by the Minister / Head of the Institution in charge of government affairs in the field of research, development, assessment, and application as well as integrated invention and innovation.